Penyuluhan Perilaku Hidup Bersih dan Sehat (PHBS) SD N Bukit Permai Kabupatan Sumbawa - Hamdin Hamdin; Abdul Hamid (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
Clean and Healthy Living Behavior (PHBS) is an effort to create conditions for individuals, families, groups and communities in attitudes and behavior so that they can implement healthy living in order to maintain, maintain and improve health status. PHBS in schools is the implementation of certain health procedures by empowering teachers, students and the community in the school environment. The aim is to increase students' awareness of being able to implement PHBS in schools. Method This community service activity is carried out in the form of counseling using power point and LCD presentation media. The methods used are in the form of counseling, discussions and questions and answers with Bukit Permai Elementary School students. The results obtained from this community service activity are that the students' knowledge has increased regarding Clean and Healthy Living Behavior both at school and at home. This can be seen from the large number of responses from students in answering questions given by the presenter